Ships and sailors : tales of the sea - Rogers, Stanley, 1887-1961. (Tufts University. Tisch Library., 2024)
Table of Contents: Part I: Shipwrecks -- The "Centaur" : the "Halswell" : the "Grosvenor" -- The "Wager" : the "Strathmore" -- The "Kent" : the "Endurance" : The thirty-two whalers -- Part II: Mutinies and sea-fights -- The "Dreadnought" and "Bounty" mutinies -- The "Globe" : the "Sharon" : the Spithead mutiny -- The recapture of the "Exchange" : Pierre le Grand : the "Revenge" -- Part III: Remarkable boat journeys -- Shackleton's journey : the boats of the "Essex" -- The "Bounty" castaways : the "Trevessa's" boats : the "Earl of Eldon" -- The "Tilkum" : the "Lady Hobart's" boats -- Part IV: Sea mysteries -- The "Mary Celeste" : the "Waratah" : the "President" : Sir John Franklin -- The lost frigates, and other sea mysteries -- The "Flying Dutchman" : Whale stories : Sea-serpants and other superstitions -- Part V: Pirates and treasure-ships -- Buccaneers and pirates -- More pirates -- Treasure-ships.; Includes index.